2016
DOI: 10.2337/db16-0166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-451 Negatively Regulates Hepatic Glucose Production and Glucose Homeostasis by Targeting Glycerol Kinase–Mediated Gluconeogenesis

Abstract: MicroRNAs (miRNAs) are a new class of regulatory molecules implicated in type 2 diabetes, which is characterized by insulin resistance and hepatic glucose overproduction. We show that miRNA-451 (miR-451) is elevated in the liver tissues of dietary and genetic mouse models of diabetes. Through an adenovirus-mediated gain- and loss-of-function study, we found that miR-451 negatively regulates hepatic gluconeogenesis and blood glucose levels in normal mice and identified glycerol kinase (Gyk) as a direct target o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
3
42
0
Order By: Relevance
“…The apparent opposite effects of miR-144/451 (alleviation of I/R-induced heart injury and promotion of HFD-induced cardiac hypertrophy) suggest that 1) miR-144 and miR-451, though produced from the same gene, might function differently; 2) the same miRNA could participate in gene regulation in a compartment-dependent or disease-dependent manner, where the latter is evidenced by our recent finding that miR-451 inhibits the same Cab39/LKB1/AMPK signaling pathway but with opposite cellular effects: protection of red cells against apoptosis [46] vs lipotoxicity in cardiomyocytes [90]. Another metabolism-related study demonstrates that HFD or diabetic condition induces the expression of hepatic miR-451 [91]. Glucose or insulin also upregulates miR-451 in hepatocytes, which leads to the inhibition of hepatic gluconeogenesis and thus low blood glucose levels [91].…”
Section: Function Of Mir-144/451 In Additional Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent opposite effects of miR-144/451 (alleviation of I/R-induced heart injury and promotion of HFD-induced cardiac hypertrophy) suggest that 1) miR-144 and miR-451, though produced from the same gene, might function differently; 2) the same miRNA could participate in gene regulation in a compartment-dependent or disease-dependent manner, where the latter is evidenced by our recent finding that miR-451 inhibits the same Cab39/LKB1/AMPK signaling pathway but with opposite cellular effects: protection of red cells against apoptosis [46] vs lipotoxicity in cardiomyocytes [90]. Another metabolism-related study demonstrates that HFD or diabetic condition induces the expression of hepatic miR-451 [91]. Glucose or insulin also upregulates miR-451 in hepatocytes, which leads to the inhibition of hepatic gluconeogenesis and thus low blood glucose levels [91].…”
Section: Function Of Mir-144/451 In Additional Tissuesmentioning
confidence: 99%
“…Another metabolism-related study demonstrates that HFD or diabetic condition induces the expression of hepatic miR-451 [91]. Glucose or insulin also upregulates miR-451 in hepatocytes, which leads to the inhibition of hepatic gluconeogenesis and thus low blood glucose levels [91]. Again, a negative feedback between glucose and miR-451 assures the maintenance of normal levels of blood glucose.…”
Section: Function Of Mir-144/451 In Additional Tissuesmentioning
confidence: 99%
“…Studies have also indicated links between Gyk and the regulation of glucose homeostasis; specifically, it is overexpressed in response to thiazolidinediones, drugs commonly used to treat type 2 diabetes mellitus (7), and this overexpression relieves insulin resistance (8,9). Gyk was recently identified as a target of microRNA-451, which regulates gluconeogenesis through both the glycerol-gluconeogenic axis and the protein kinase B (AKT)-FOXO1-phosphoenolpyruvate carboxykinase/ G6Pase pathway (10). Therefore, mammalian Gyk is a pleiotropic enzyme with a myriad of functions, not all of which have been fully characterized.…”
mentioning
confidence: 99%
“…As Chen et al (29) reported, under metabolic stress, miR-17-92 regulated glucose-stimulated insulin secretion and pancreatic β-cell adaptation. By inhibiting glycerol kinase, miR-451 negatively regulated hepatic gluconeogenesis and blood glucose levels in diabetes (30). Fu et al (31) reported that miR-26a was downregulated in two obese mouse models and regulated insulin signaling and metabolism of glucose.…”
Section: Discussionmentioning
confidence: 99%